Pronounced centennial-scale Atlantic Ocean climate variability correlated with Western Hemisphere hydroclimate - Kaustubh Thirumalai (Nature Portfolio, 2018)
Knowledge of surface-ocean circulation in the Atlantic over the late Holocene is incomplete. Here, the authors show that Atlantic Ocean surface-circulation varied in concert with Western Hemisphere rainfall anomalies on centennial timescales and that this link played an essential role during the Little Ice Age.